Analisis Aplikasi Digital dalam Optimalisasi Laporan Keuangan UMKM - Tasya Patmawati; Karyadi (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
One of the drivers of the Indonesian economy is micro, small and medium enterprises (MSMEs). Business actors are increasingly developing in all things, especially finance, along with advances in time and technology. Good financial recording is the most important part of a business. If the business owner has neat and correct financial resources, then he will have no difficulty applying for capital or credit to the bank. An analysis has been carried out on the use of digital applications to improve MSME financial reporting in accordance with technological developments. This research was conducted with direct insight, aiming to find out the best way to manage the finances of small and medium MSME businesses so that they can produce neat financial reports. MSMEs are advised to have non-cash payment tools such as EDC & Qris machines to make it easier and keep up with technological developments, with non-cash payments it can make it easier to make financial reports.